Assessment of The Potential Utilization of Urban Forests as A Public Recreational Area (Case Study in Kibitay Urban Forest, Sukabumi City) - Suciyani, Wida Oktavia; Utami, Fadhilah Noordya; Bakhti, Krisna Yudha; Putri, Sherly Raka Siwi (Jurnal Pembangunan Wilayah dan Kota, 2023)
The urban forest can provide social benefits as a public recreation area. Efforts to utilize the urban forest as a recreational area need to be carefully planned, so it is necessary to assess the recreational potential of the urban forest to produce effective planning. This study aims to reveal in depth the potential utilization of urban forest assets as a public recreation area based on the determination of outdoor recreation potential. The study method used is descriptive qualitative and quantitative with data collection techniques, including observation, interviews, and documentation studies. Based on the results of the assessment, it is revealed that the recreational potential of the Kibitay Urban Forest assets is included in the high recreational potential category by 64% because it has sufficient landscape feature value and high climate value and accessibility. This shows that the Kibitay Urban Forest has the potential to be used as a public recreation area, although recreational facilities are not fully adequate. Future research can consider conducting asset planning for Kibitay Urban Forest facilities in Sukabumi City as a public recreation area.